A Simple Approach to Interest-Rate Option Pricing - Turnbull, Stuart M.; Milne, Frank (Review of Financial Studies, 1991)
A simple introduction to contingent claim valuation of risky assets in a discrete time, stochastic interest-rate economy is provided. Taking the term structure of interest rates as exogenous, closed-form solutions are derived for European options written on (i) Treasury bills, (ii) interest-rate forward contracts, (iii) interest-rate futures contracts, (iv) Treasury bonds, (v) interest-rate caps, (vi) stock options, (vii) equity forward contracts, (viii) equity futures contracts, (ix) Eurodollar liabilities, and (x) foreign exchange contracts.